Manometry of the Human Ileum and Ileocaecal Junction in Health, Disease and Surgery: A Systematic Review - Liu, Chen; Saw, Kai Sheng; Dinning, Phil G.; O'Grady, Gregory; Bissett, Ian (Frontiers in Surgery, 2020)
Background The terminal ileum and ileocaecal junction form a transition zone in a relatively inaccessible portion of the gastrointestinal tract. Little is known about the motility of this region with few detailed studies, indicating the need for a robust synthesis of current knowledge. This review aimed to evaluate the quantitative and qualitative data on the manometry findings of the terminal ileum and ileocaecal junction during the fasting and post-prandial periods in healthy individuals and patients with motility disorders or patients after bowel surgery. Methods A systematic search of five databases (Medline, Pubmed, Embase, Scopus and Cochrane Library) was performed. Studies that presented manometry data from the human ileum or ileocaecal junction were included. Results Forty-two studies met the inclusion criteria. The main motility patterns reported in the terminal ileum during fasting were the migrating motor complex, discrete clustered contractions, prolonged propagated contractions and phasic contractions. Post-prandial motility featured irregular, intense contractions. Some studies found a region of sustained increased pressure at the ileocaecal junction while others did not. Patients with motility disorders showed differences in manometry including retrograde propagation of phase III. Patients post-bowel surgery showed differences including higher incidence of phase III. Conclusion Motility patterns of the terminal ileum differ between fasting and fed states. Large variability existed in manometry recordings of the terminal ileum. Technical challenges and lack of standardized definitions may reduce accuracy of manometry assessment. Further research is needed to understand how this key portion of the gut physiologically functions.